Klasifikasi Mobil berjalan dan Pejalan Kaki untuk Penggunaan Automatic Incident Detection Sebagai Upaya Pengurangan Resiko Kecelakaan di Jalan Raya - Herry Setiawan; Amsar Yunan (Jurnal Inotera, 2020)
Traffic problems become very important to minimize the number of accidents. Recorded in 2017, the death toll from accidents reached 703 people. While in 2018 503 people died or fell by 28%. This figure is considered to be the third largest killer, under coronary heart disease and tuberculosis / tuberculosis. Among several causes of accidents such as against the flow of traffic, stops on the road, pedestrians and speeds that are too low compared to other vehicles. Even though the traffic signs are already installed. The low level of awareness of road users will increase the number of accidents. A detection system for potential accidents is needed to reduce the risk and can be used for the investigation process if an accident occurs. The application of a traffic accident prediction system will be a solution to provide a warning of potential accidents. Early detection of incidents is very important to limit consequences such as delays for other road users, lower costs, less time commitment to emergency services, as well as to prevent accidents. Video processing obtained from CCTV installed at intersections, highways, bridges and tunnels will detect pedestrians and oncoming cars automatically. Detection is done by processing each video frame to determine the foreground by the Gaussian mixture models method of each video frame.